Second Five Year Plan Bombay State Baroda District - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Plan (1956–61) for Baroda District, Bombay State, presents a comprehensive framework for socio-economic development, emphasizing agriculture, education, infrastructure, health, housing, and social welfare. Agricultural initiatives focus on enhancing productivity through improved seeds, fertilizers, irrigation systems, crop protection measures, and modern farming techniques, with significant attention to cotton, tobacco, and bajri cultivation. Education is a central pillar of the plan, incorporating compulsory primary education, vocational training, literacy campaigns, secondary and technical education, and expansion of university faculties at Maharaja Sayaji Rao University. Infrastructure development encompasses road networks, bridges, and rural electrification under the North Gujarat Electric Grid Scheme to facilitate connectivity and economic growth. Health and sanitation improvements include expansions of civil hospitals, establishment of leprosy control centers, and integration of preventive and curative services to cover large populations. Housing programs target industrial workers and low-income families through state-supported tenements and cooperative schemes. Labor welfare initiatives focus on improving standards through educational and recreational programs, while backward class communities receive targeted support via scholarships, agricultural assistance, and craft training schools. Community participation is promoted through the establishment of local panchayats and cooperatives to empower rural governance and economic engagement. Collectively, the plan reflects a holistic approach to sustainable development, aiming to elevate living standards, foster inclusive growth, and create a robust foundation for long-term socio-economic progress in Baroda District.
Baroda District
Baroda District
Keywords: State Five Year Plan; Baroda District Development; Agricultural Productivity; Irrigation Projects; Primary and Secondary Education; Technical and University Education; Health and Sanitation; Housing Initiatives; Labor Welfare; Backward Classes Support; Infrastructure Development; Community Participation